PRELIMINARY REFERENCE PROCEDURE AND THE SCOPE OF JUDICIAL REVIEW OF THE EUROPEAN COURT OF HUMAN RIGHTS (EU and comparative law issues and challenges series (ECLIC), 2019)
The purpose of this paper is to examine the scope of the ECtHR’s review of preliminary reference procedure provided for in Article 267 TFEU, insofar as it concerns the right to a fair trial and other procedural safeguards read into substantive rights of the ECHR. In Ullens de Schooten and Rezabek v. Belgium, the ECtHR established the principles of its review under Article 6(1) ECHR in connection to the obligation of the national courts to refer the question for a preliminary ruling. This paper analyses the scope of protection of the right to a fair trial in the context of the national court’s failure to refer a question to the CJEU for a preliminary ruling, in particular in the light of the CJEU’s Cilfit case law and additional obligations imposed on the national courts by the ECtHR that supplement the standards set out in the CJEU’s jurisprudence. The reason behind circumventing the applicability of the right to an effective remedy (Article 13 ECHR) to the preliminary reference procedure is being ellaborated as well, especially with respect to the CJEU’s finding that a request for preliminary ruling does not constitute a mean of redress available to the parties. Furthermore, this paper discusses whether the preliminary reference procedure can be considered as a procedural safeguard read into substantive rights of the ECHR. In connection to the latter, the interrelation between preliminary reference procedure and two principles - the principles of subsidiarity and equivalent protection - is analysed.